Pengaruh Orang, Proses, Kualitas Layanan dan Nilai Pelanggan Terhadap Kepuasan Pelanggan Pada PT Prudential Life Assurance Pontianak - Mochammad Faisal Fadli (Jurnal Ekonomi Integra, 2017)
This type of research is Causal explanatory is a type of research that aims to determine the pattern of the relationship between variables as hypothesis testing. The data analysis technique used is the technique of data analysis path analysis (Path Analysis). Based on the data processing using path analysis, it is evident that the people, processes and service quality effect on customer value and people, process, service quality and customer value is also positive and significant impact on customer satisfaction at Prudential Life Assurance Pontianak with customer value as an intervening variable.